Cu‐Rich Precursors Improve Kesterite Solar Cells. Issue 2 (19th September 2013) - Mousel, Marina; Schwarz, Torsten; Djemour, Rabie; Weiss, Thomas P.; Sendler, Jan; Malaquias, João C.; Redinger, Alex; Cojocaru‐Mirédin, Oana; Choi, Pyuck‐Pa; Siebentritt, Susanne
<x xml:space="preserve">Abstract</x> A precursor‐annealing process based on a Cu‐rich precursor that has a maximum power conversion efficiency of 7.5% for pure selenide kesterite cells is presented. The Cu‐rich step is beneficial for the transport properties. Nanometer‐sized domains of ZnSe are found in all films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>